Opłacalność inwestowania w elektrownie wiatrowe - Pultowicz, Alicja Małgorzata (Profitability of Investing in Wind Turbines, 2005)
The main issue of this article is to emphasize how financial risk, time of amortization and paying credit, investment and operating costs influence profitability of wind power farms. The first part concerns the main factors responsible for the level of wind energy prices. Investment and operating costs are presented in the second part of the article. Wind energy sector was characterized by very dynamic development rate in the last decade. In comparison to Germany, the world leader, Poland has almost the same wind conditions what can result in further and wider development of this sector. However, the main obstacles are lack of required energy price and direct financial support from the government.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonomia i Międzynarodowe Stosunki Gospodarcze (11); 2005; nr 1077, s. 111-123